Public Trust in the Mass Media - Ramli; Muahammad Anshar Akil (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The Journalistic Code of Ethics is an important guide for journalists in carrying out their profession with the aim of maintaining integrity, objectivity, and public trust in the mass media. This article discusses the basic principles of the Journalistic Code of Ethics including independence, accuracy, fairness and social responsibility. In addition, this article also analyzes the application of the code of ethics in journalistic practices in Indonesia as well as the challenges faced by journalists in complying with these ethical standards in the digital era where information can be easily disseminated through various social media platforms. The study uses a qualitative approach through literature analysis and interviews with media practitioners to gain an in-depth understanding of the importance of this code of ethics in maintaining journalists' professionalism and public trust. The results of this study show that compliance with the Journalistic Code of Ethics can increase media credibility and build a better relationship between the media and the audience.